Pengaruh Citra Destinasi Dan Atribut Destinasi Terhadap Minat Berkunjung Ulang Wisatawan Ke Destinasi Wisata Alahan Panjang - Anggi Takila Rahmania; Youmil Abrian (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
This research was motivated by the intention phenomenon to revisit the Alahan Panjang destination. The length is influenced by the tourist destination image and the attributes of the tourist destination in Alahan Panjang. Several tourist reviews state that the tourist destination Alahan Panjang is not Recommended for those who re-visit and haven't experienced the attraction yet impressive for tourists. This research aims to analyze the tourist destination image and attributes of the Alahan Panjang tourist destination. In this research using quantitative methods, the research type used in this research is causal associative or cause-effect relationships. Data was obtained from survey results by distributing questionnaires to respondents which is the object of research. The average for the tourist destination image variable is 4.112 with criteria Good. The tourist destination attribute variable has an average of 3.996 with Good criteria. Then The tourist destination attribute variable has an average of 4.016 with Good criteria. So therefore There is a positive and significant influence between the image of a tourist destination and interest in visiting repeated the tourist. There is also an influence between tourist destination attributes and interest in visiting repeated the tourist. Destination image variables and tourist destination attributes have an impact on variable interest in revisiting, then H1, H2 and H3 are accepted.